Catecholase and phenoxazinone synthase activities of a ferromagnetically coupled tetranuclear Cu(II) complex - Mitra, Merry; Kundu, Tanay; Kaur, Gurpreet; Sharma, Gyaneswar; Choudhury, Angshuman Roy; Singh, Yogesh; Ghosh, Rajarshi (RSC Advances, 2016)
A crystallographically characterized tetranuclear Cu(II) complex [Cu-4(II)(L)(4)] (1) [H2L = N-(2-hydroxyethyl)-3-methoxysalicylaldimine] is found to show overall ferromagnetic exchange coupling. Complex (1) mimics the catalytic activity of the plant enzyme catechol oxidase by oxidising 3,5-di-tert-butylcatechol to its corresponding quinone in methanol and dichloromethane medium in the presence of aerial oxygen. The reaction follows Michaelis-Menten enzymatic reaction kinetics with turnover numbers (K-cat) 6.99 x 10(3) and 1.85 x 10(3) h(-1) in methanol and dichloromethane, respectively. 1 is also phenoxazinone synthase active in methanol medium with a turnover number of 1.21 x 10(5) h(-1).